2017
DOI: 10.1002/elps.201700145
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of capillary zone electrophoresis for charge heterogeneity testing of biopharmaceuticals using enhanced method development principles

Abstract: CZE is a well‐established technique for charge heterogeneity testing of biopharmaceuticals. It is based on the differences between the ratios of net charge and hydrodynamic radius. In an extensive intercompany study, it was recently shown that CZE is very robust and can be easily implemented in labs that did not perform it before. However, individual characteristics of some examined proteins resulted in suboptimal resolution. Therefore, enhanced method development principles were applied here to investigate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…It has been shown that the BGE used here is close to the optimum for charge heterogeneity profiling of mAbs . However, peak deteriorations during initial experiments conducted with a mixture of antibody and antigen (data not shown) led to the assumption that there is a strong capillary wall adhesion of the antigen under separation conditions as results were similar to other publications on this problem .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It has been shown that the BGE used here is close to the optimum for charge heterogeneity profiling of mAbs . However, peak deteriorations during initial experiments conducted with a mixture of antibody and antigen (data not shown) led to the assumption that there is a strong capillary wall adhesion of the antigen under separation conditions as results were similar to other publications on this problem .…”
Section: Resultssupporting
confidence: 82%
“…These compounds prevent excessive Joule heating, reduce EOF and dynamically coat the inner capillary wall. Further investigations with different mAbs have demonstrated the generic applicability of this method and have shown some important parameters for the development of tailor‐made adaptions . An international cross‐laboratory study has demonstrated that CZE is a simple, fast, reliable, and reproducible method for the relative quantification of different charge species .…”
Section: Introductionmentioning
confidence: 96%
“…Design of experiments (DoE) is usually part of such a concept and serves as a valuable tool to gain maximal knowledge about adjustable factors within a defined range. In addition, DoE is increasingly used for other analytical tasks, especially for method optimization .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, increasing efforts have been made to directly hyphenate IEC , CZE and recently iCIEF to mass spectrometry (MS), to quickly identify charge variants at the mAb intact level. However, compromises on the separation performance are often made when directly coupling the LC and CE methods to MS, which explain why CZE‐UV methods are still being developed and applied in the biopharmaceutical industry .…”
Section: Introductionmentioning
confidence: 99%
“…The EOF and protein adsorption can be limited with (i) the use of static capillary wall coatings or more generally with (ii) a dynamic coating . Most of the CZE methods listed in the review of Gahoual et al .…”
Section: Introductionmentioning
confidence: 99%